Rapid colorimetric assay based on the oxidation of 2,2-azino-bis(3-ethylbenzothiazoline)-6-sulfonic acid-diammonium salt for nitrite detection in meat products - Jantra, Jongjit; Arsawiset, Supattra; Teepoo, Siriwan; Keeratirawee, Kanchalar (My University, 2024)
This work developed a rapid colorimetric method for nitrite detection in meat products. The detection was based on the reaction of nitrite with 60 mM HCl to produce radicals which further oxidized ABTS (50 µM) to form a water-soluble blue-green product (ABTS•+). The absorbance was measured at a maximum absorption wavelength of 412.5 nm. Parameters such as concentration of HCl, concentration of ABTS and reaction time were evaluated. The absorbance was linearly proportional to the concentration of nitrite (0.1–20 µM) with the limit of detection of 0.34 µM. The proposed method was a time-saving assay since it required only 2 min to complete one measurement. There was no effect of the interference produced by other ions. The assay was robust with 2.5%RSD (n = 50). In meat product samples, high accuracy was observed with the recoveries between 100 ± 2.2% and 105 ± 3.7%. The amount of nitrite in meat products detected by the ABTS method was found in the range of 5.41 − 7.62 mg/kg. The conventional Griess method was applied to determine nitrite in the same meat products. There was no statistically significant difference between the two methods (P = 0.05).
Keywords: ABTS; chemical sensor; colorimetric; food contaminant; Nitrite; sausage; spectrophotometry